'Go to sleep, Mammy's little baby' 'East Hull lullaby' - Awre, Gabrielle; Christina (The University of Hull, 2017)
Chris sings a lullaby she learnt as a child in East Hull. At the time of recording she thought this was an original song from her family. The words and music have since been traced to a song written in 1890 or 1893 by Hattie Starr called 'My Alabama Coon', aka 'Go to sleep my little piccaninny', also linked to a later version called 'Stay in your own back yard', https://egrove.olemiss.edu/sharris_a/22/